Palaeopathological and demographic data reveal conditions of keeping of the ancient baboons at Gabbanat el-Qurud (Thebes, Egypt) - Van Neer, Wim; Udrescu, Mircea; Peters, Joris; De Cupere, Bea; Pasquali, Stéphane; Porcier, Stéphanie (PLOS ONE, 2023)
Since predynastic times, baboons (Papio hamadryas and Papio anubis) were important in ancient Egypt for ritual and religious purposes. These species did not occur naturally in Egypt and therefore had to be imported, but little is known about their exact provenance and the conditions in which they were kept through time. Here, we analyse the skeletal remains of a collection of baboon mummies coming from Thebes (Egypt), representing a minimum of 36 individuals, from a palaeopathological and demographic point of view. The pathological cases are described, figured where relevant, and the discussion attempts to understand their aetiology. The prevalence of the different types of deformations and pathologies is compared with that of other captive baboon populations from more or less contemporary (Tuna el-Gebel and Saqqara) or older (predynastic Hierakonpolis) sites. This is combined with observations on the age and sex distribution and the proportion of hamadryas and anubis baboons to draw conclusions about the conditions of keeping, possible breeding on-site, provenance of the animals and the trade routes used for import. As in Tuna el-Gebel and Saqqara, the baboons from Gabbanat el-Qurud suffered from numerous metabolic diseases due to chronic lack of sunlight and an unbalanced diet. This and the demographic data suggest that there was a local breeding population derived from animals captured downstream from the Sudanese Nile Valley (for anubis) and from the Horn of Africa or the southern part of the Arabian Peninsula (for hamadryas). A new series of radiocarbon dates is provided, placing the baboons from Gabbanat el-Qurud between the end of the Third Intermediate Period and the beginning of the Late Period.